Patterns of molecular motors that guide and sort filaments - Rupp, Beat; Nédélec, François (Lab on a chip, 2012)
Molecular motors can be immobilized to transport filaments and loads that are attached to these filaments inside a nano-device. However, if motors are distributed uniformly over a flat surface, the motility is undirected, and the filaments move equally in all directions. For many applications it is important to control the direction in which the filaments move, and two strategies have been explored to achieve this: applying external forces and confining the filaments inside channels. In this article, we discuss a third strategy in which the topography of the sample remains flat, but the motors are distributed non-uniformly over the surface. Systems of filaments and patterned molecular motors were simulated using a stochastic engine that included Brownian motion and filament bending elasticity. Using an evolutionary algorithm, patterns were optimized for their capacity to precisely control the paths of the filaments. We identified patterns of motors that could either direct the filaments in a particular direction, or separate short and long filaments. These functionalities already exceed what has been achieved with confinement. The patterns are composed of one or two types of motors positioned in lines or along arcs and should be easy to manufacture. Finally, these patterns can be easily combined into larger designs, allowing one to precisely control the motion of microscopic objects inside a device.